2002
DOI: 10.1038/sj.ijo.0801840
|View full text |Cite
|
Sign up to set email alerts
|

Increased visceral fat distribution in drug-naive and drug-free patients with schizophrenia

Abstract: OBJECTIVE:To investigate visceral fat distribution in patients with schizophrenia. DESIGN: Cross sectional study using CT scanning in patients with drug-naive and drug-free schizophrenia. SUBJECTS: Fifteen (13 men and two women) subjects with schizophrenia (mean age 33.7 y; mean body mass index (BMI) ¼ 26.7 kg=m 2 ), and 15 age-and sex-matched controls (mean age 30.5 y; mean BMI ¼ 22.8 kg= 2 ). MEASUREMENTS: Various fatness and fat distribution parameters (by CT scanning and anthropometry) and 16:00 h plasma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
1
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(198 citation statements)
references
References 41 publications
5
171
1
20
Order By: Relevance
“…The basic mechanisms behind these metabolic irregularities have not been fully elucidated, but it appears that antipsychotic medications could play an important role (Newcomer, 2005). Moreover, high rates of obesity and type II diabetes mellitus, observed in drug-naive/free patients (Mukherjee et al, 1996;Allison et al, 1999a;Thakore et al, 2002;Ryan et al, 2003Ryan et al, , 2004 before Kohen, 2004) and after the advent of antipsychotics and in nonschizophrenic blood relatives (Dynes, 1969;Mukherjee et al, 1989;Cheta et al, 1990;Martins et al, 2001;Lamberti et al, 2004), were potentially attributed to genetic factors (Stone et al, 2004), illness neurobiology (Thakore, 2005) and to unhealthy lifestyle (Brown et al, 1999). The interpretability of the preneuroleptic era data (reviewed in Kohen, 2004) is, however, limited by flaws in epidemiological methodology including lack of evaluation of and adjustments for adiposity, lifestyle, and anthropometric measures together with inconsistent diagnostic criteria for schizophrenia and glucose/insulin abnormalities Newcomer, 2005).…”
Section: Weight Status Of Drug Naive/free Schizophrenic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic mechanisms behind these metabolic irregularities have not been fully elucidated, but it appears that antipsychotic medications could play an important role (Newcomer, 2005). Moreover, high rates of obesity and type II diabetes mellitus, observed in drug-naive/free patients (Mukherjee et al, 1996;Allison et al, 1999a;Thakore et al, 2002;Ryan et al, 2003Ryan et al, , 2004 before Kohen, 2004) and after the advent of antipsychotics and in nonschizophrenic blood relatives (Dynes, 1969;Mukherjee et al, 1989;Cheta et al, 1990;Martins et al, 2001;Lamberti et al, 2004), were potentially attributed to genetic factors (Stone et al, 2004), illness neurobiology (Thakore, 2005) and to unhealthy lifestyle (Brown et al, 1999). The interpretability of the preneuroleptic era data (reviewed in Kohen, 2004) is, however, limited by flaws in epidemiological methodology including lack of evaluation of and adjustments for adiposity, lifestyle, and anthropometric measures together with inconsistent diagnostic criteria for schizophrenia and glucose/insulin abnormalities Newcomer, 2005).…”
Section: Weight Status Of Drug Naive/free Schizophrenic Patientsmentioning
confidence: 99%
“…Seeking to tackle serious methodological limitations of the early research, Thakore et al (2002) applied a wellvalidated technique of computed tomography (Mayo-Smith et al, 1989) to directly measure abdominal adiposity in a sample of drug-naive/free schizophrenic patients and ageand sex-matched healthy controls. They found that schizophrenic patients had higher body mass index (BMI) and over three times more abdominal fat , accumulation of which poses even greater cardiovascular/ diabetes risks than overall obesity .…”
Section: Weight Status Of Drug Naive/free Schizophrenic Patientsmentioning
confidence: 99%
“…Studies of Irish first-episode psychosis patients have shown that they are more insulin-resistant and have higher fasting blood glucose concentrations than carefully matched controls [55]. Patients also have more intraabdominal fat and hypercortisolaemia, suggesting that schizophrenia in itself is associated with an increased risk of diabetes [56]. These findings have not been replicated in Chinese and Spanish populations, but methodological and subject differences may explain this discrepancy [57,58].…”
Section: Specificity Of Associationmentioning
confidence: 99%
“…However, the results of these analyses may have been biased because some patients with very low or very high BMI, as well as those with significant medical illness, were excluded. Efforts to study this phenomenon in patients who are drug naïve or early in treatment compared to age-and sex-matched controls have been limited and yielded mixed results: some but not all (Ryan et al, 2004;Zhang et al, 2004a) studies found higher BMI in patients, and some (Ryan et al, 2004;Thakore et al, 2002) but not all (Zhang et al, 2004a) studies found higher intra-abdominal fat (IAF) in patients.…”
Section: Introductionmentioning
confidence: 99%